Novel Therapeutic Approaches in Treatment of Acute-on-Chronic Liver Failure - Saeidinejad, MohammadMahdi; Elshabrawi, Ahmed; Sriphoosanaphan, Supachaya; Andreola, Fausto; Mehta, Gautam; Agarwal, Banwari; Jalan, Rajiv (Seminars in Liver Disease, 2023)
Acute-on-chronic liver failure (ACLF), a clinical syndrome that can develop at any stage in the progression of cirrhotic liver disease, is characterized by an acute decompensation in liver function with associated multiorgan failure and high short-term mortality. Current evidence points to ACLF being reversible, particularly in those at the lower end of the severity spectrum. However, there are no specific treatments for ACLF, and overall outcomes remain poor. Expedited liver transplantation as a treatment option is limited by organ shortage and a lack of priority allocation for this indication. Other options are therefore urgently needed, and our improved understanding of the condition has led to significant efforts to develop novel therapies. In conclusion, this review aims to summarize the current understanding of the pathophysiological processes involved in the onset, progression, and recovery of ACLF and discuss novel therapies under development.
Keywords: cirrhosis; ACLF; Inflammation